Are positive teachers’ attitudes crucial for the achievement of successful inclusive education? - Wong Sato, Aisa (2020)
Teachers’ positive attitudes towards inclusive education are seen as one of the main components to the successful inclusion of special educational needs (SEN) students in mainstream schools, therefore, many studies have focused on this phenomena. However, not much research can be found from the student perspective on how teachers’ attitudes affect their well-being. The aim of this study was to explore at what level teachers’ attitudes are able to significantly impact the success of inclusive education. In this case, the success was defined by the social well-being of students in inclusive classrooms according their own perception of their relationships with their peers and teachers. Data for this research were taken from a larger Finnish study, ProKoulu, This study analysed teacher and student data. The teacher data consists of the responses of 403 teachers on their attitudes and concerns towards inclusive education and their perception of classroom diversity (number of SEN students per classroom). Student data were aggregated from 455 classrooms to obtain a mean value of students’ social well-being per classroom. The results showed that teachers’ attitudes have a very minor role in the success of inclusive education, at least when evaluated through the social well-being of Finnish students. Attitudes displayed a small moderation effect, making it unclear how relevant positive teachers’ attitudes are for inclusive education, especially in the Finnish context.